A Prospective Study of Musculoskeletal Outcomes Among Manufacturing Workers: I. Effects of Physical Risk Factors. (February 2014) - Gerr, Fredric; Fethke, Nathan B.; Merlino, Linda; Anton, Dan; Rosecrance, John; Jones, Michael P.; Marcus, Michele; Meyers, Alysha R.
Objective: To better characterize associations between physical risk factors and upper-extremity musculoskeletal symptoms and disorders, a prospective epidemiologic study of 386 manufacturing workers was performed. Background: Methodological limitations of previous studies have resulted in inconsistent associations. Method: An individual, task-based exposure assessment strategy was used to assess upper-extremity exertion intensity, repetition, and time-in-posture categories. Participants recorded time spent performing daily work tasks on a preprinted log, which was then used to calculate time-weighted-average exposures across each week of follow-up. In addition, a weekly Strain Index (SI) risk category was assigned to each participant. Incident musculoskeletal symptoms and disorders were assessed weekly. Proportional hazards analyses were used to examine associations between exposure measures and incident hand/arm and neck/shoulder symptoms and disorders. Results: Incident symptoms and disorders were common (incident hand/arm symptoms = 58/100 person-years (PY), incident hand/arm disorders = 19/100 PY, incident neck/shoulder symptoms = 54/100 PY, incident neck/shoulder disorders = 14/100 PY). Few associations between separate estimates of physical exposure and hand/arm and neck/shoulder outcomes were observed. However, associations were observed between dichotomized SI risk category and incident hand/arm symptoms (hazard ratio [HR] = 1.73, 95% confidence interval [CI] = [0.99, 3.04]) and disorders (HR = 1.93, 95% CI = [0.85, 4.40]). Conclusion: Evidence of associations between physical risk factors and musculoskeletal outcome was strongest when exposure was estimated with the SI, in comparison to other metrics of exposure. Application: The results of this study provide evidence that physical exposures in the workplace contribute to musculoskeletal disorder incidence. Musculoskeletal disorder prevention efforts should include mitigation of these occupational risk factors.